Synthesis of Si(IV)- and Ge(II)-substituted amines, hydrazone, and hydrazine from hypersilyl germylene - Ajithkumar, V. S.; Ghanwat, Pratiksha B.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2023)
This study investigates the reactivity of a hypersilyl germylene [PhC-(NtBu)(2)GeSi-(SiMe3)(3)] (1) with various organic compounds including azides, diazoalkanes, 1,2-diphenylhydrazine, and trifluoroacetophenone. The reactivity observed in these reactions is driven by the insertion of the organic fragment between a silicon and germanium bond. This leads to the formation of novel compounds, including an amine featuring three different substituents from three different elements of group 14. When reacting with Me3SiCHN2, we observed the insertion of the diazoalkane fragment in an end-on fashion into the Ge-Si bond. An analogous trend was observed in reactions with 1,2-diphenylhydrazine and trifluoroacetophenone, where the N-N and C-O fragments were inserted into the Ge-Si bond. Multinuclear NMR and single-crystal X-ray diffraction analyses were conducted to characterize the newly synthesized compounds.

Activation of carbon disulfide by a hypersilyl germylene - Ajithkumar, V. S.; Khilari, Nripen; Ghanwat, Pratiksha B.; Venugopal, Geethu; Koley, Debasis; Sen, Sakya S. (Dalton Transactions, 2024)
In this work, the insertion of CS2 into the Ge-Si bond of PhC(NtBu)2Ge-Si(SiMe3)3 (1) has been investigated, resulting in the formation of PhC(NtBu)2Ge-C( 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 S)-S-Si(SiMe3)3 (2). Interestingly, the addition of NHC to 2 allows the release of NHCCS2 with concomitant regeneration of 1. Addition of another equivalent of 1 or an analogous hypersilyl silylene, [PhC(NtBu)2Si-Si(SiMe3)3], to 2 led to the formation of compounds with a GeS (3) or a SiS (4) bond. In this work, the insertion of CS2 into the Ge-Si bond of PhC(NtBu)2Ge-Si(SiMe3)3 (1) has been investigated, resulting in the formation of PhC(NtBu)2Ge-C(S)-S-Si(SiMe3)3 (2).

Stereodivergent sila-germylenation vs. sila-stannylenation of an internal alkyne - Ajithkumar, V. S.; Ghanwat, Pratiksha B.; Saha, Sougata; Pati, Swapan K.; Sen, Sakya S. (CHEMICAL COMMUNICATIONS, 2024)
Keywords: DIVERSE REACTIVITY; H BOND ACTIVATION; hydrides

C=C insertion over N=C=O of allyl isocyanate into the Ge-Si bond of a germylene - Ajithkumar, V. S.; Khilari, Nripen; Ghanwat, Pratiksha B.; Koley, Debasis; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2025)
Two isocyanates are reacted with the germylene, PhC(NtBu)(2)Ge-Si(SiMe3)(3) (1). Phenyl isocyanate undergoes catalytic cyclotrimerization with 1 leading to 1,3,5-triphenyl isocyanurate (2), while allyl isocyanate undergoes both cyclotrimerization and the C=C bond insertion between the Ge-Si bond. The constitution of 3 is determined by single-crystal X-ray studies. The contrasting reactivity pattern is explained by comprehensive density functional theory studies.
Keywords: Cyclotrimerization; Density functional theory; Germylene; Insertion; isocyanates

Hypersilylsilylene-supported Ni(0) toluene and Ni(II) complexes with catalytic application - Ajithkumar, V. S.; Bisai, Milan Kumar; Ghanwat, Pratiksha B.; Raj, K. Vipin; Singh, Geetika; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2025)
The reaction of Ni(COD)2 with [PhC(NtBu)2SiSi(SiMe3)3] (1) in toluene results in the formation of an 18-electron silylene-Ni(0) toluene complex (2). The analogous reaction with 1,3-DFB instead of toluene affords the C-H activation followed by ring walking leading to the allylic cyclooctene adduct, the (eta 3-C8H13)Ni(II) complex (3). DFT calculations were carried out to elucidate the mechanism as well as to gain insight into why 1,3-DFB undergoes C-H bond activation instead of C-F bond activation. The use of NiCl2DME permits access to 16-electron (tetrylene)2NiCl2 (Si(4) and Ge(5)) species, and 4 was later used as a catalyst for the C-N coupling reaction.

Manganese(i)-catalyzed dehydrogenative borylation of terminal alkynes - Ghanwat, Pratiksha B.; Bora, Debashree; Pandya, Rinu; Vanka, Kumar; Saha, Biswajit; Sen, Sakya S. (Dalton Transactions, 2025)
Compounds containing carbon-boron bonds serve as valuable intermediates for constructing more complex molecules by transforming these bonds into other carbon-element bonds. The catalytic dehydrogenative borylation of carbon-hydrogen bonds using HBpin presents an appealing method for synthesizing carbon-boron bonds. While this approach has been extensively explored with noble metals for various types of carbon-hydrogen bonds, its application with manganese-based catalysts remains rare. This study explores a dehydrogenative borylation process employing an Earth-abundant transition metal catalyst, FcbpyMn(CO)3Br (Mn(i)), in combination with HBpin under mild conditions. Arylalkynes featuring electron-withdrawing, electron-donating, and heteroaryl substituents yielded good to excellent results. Thorough DFT calculations were performed to understand the mechanism.